2009
DOI: 10.1007/s00586-009-1013-x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of amniotic membrane to reduce postlaminectomy epidural adhesions

Abstract: Postlaminectomy epidural adhesion is implicated as a main cause of ''failed back surgery syndrome'' and associated with increased risk of complications during revision surgery. Various materials acting as mechanical barriers to reduce fibroblasts infiltration into epidural space have met with limited success. In present research, amniotic membrane (AM) was studied to investigate its effects on reducing epidural scar adhesion after laminectomy in a canine model. Laminectomy sites were created at L-1, L-3, L-5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 35 publications
1
72
0
Order By: Relevance
“…It is possible to remove extensive epidural scar adhesions and release the tethered nerve roots with revision surgery but the adhesions unfortunately recur afterwards (25,26). A treatment that can reduce epidural fibrosis and scar adhesions reliably and without side effects is therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to remove extensive epidural scar adhesions and release the tethered nerve roots with revision surgery but the adhesions unfortunately recur afterwards (25,26). A treatment that can reduce epidural fibrosis and scar adhesions reliably and without side effects is therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…The number of fibroblasts was counted and the average recorded for all 12 rats (2 laminectomy level in each rat, with one being treatment group and the other control group), repeating the procedure for three fields per sample (one from the middle of the laminectomy area and two from the margins, one on each side). The cell counting resulting for each group was expressed in cell number per mm 2 (Tao and Fan, 2009). …”
Section: Histopathological Examinationmentioning
confidence: 99%
“…Amniotic membrane has inherent properties including being immune privileged, and having the ability to modulate inflammation and reduce scar tissue formation [2][3][4][5]. Such properties present significant therapeutic potential for use of amniotic membrane during wound healing, tissue repair, and regenerative therapy [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that implanting amniotic membrane reduces postlaminectomy epidural adhesions, as well as periotoneal adhesions [3,12].…”
Section: Introductionmentioning
confidence: 99%